Exploring multilingual Code-Switching in Malaysia through We-Media Perspectives - Chong, Pei Qi; Ting, Hie Ling; Chan, Jie Yan; Lee, Sek Yui; Tay, Stephanie Cin Wun (Universitas Negeri Malang, 2023)
With the continuous development of globalization, the close contact of multiple languages has promoted the emergence of a large number of code-switching phenomena. Malaysia has the characteristics of multi-ethnic, multi-cultural and multi religious integration, which determines the phenomenon of multilingual culture in Malaysia. Malaysians use many languages to communicate. Therefore, multilingual code switching has become a unique language communication mode in Malaysia. Starting from the actual situation in Malaysia, this paper uses the video